Architecture and Algorithm of Formation control of Multi-unmanned vehicles Based on Swarm intelligence. Issue 1 (January 2021) - Tian, Z Y; Su, B; Song, W L; Fu, R; Lu, P Y; Li, J Y; Bai, C Q; Xiang, S; Gao, T Y
Abstract: The main contents of this dissertation are the application of swarm intelligence to multi-unmanned vehicle system and the realization of cooperative control of multi-unmanned vehicle system. Firstly, this thesis introduces the research background and significance of multi-unmanned vehicle system and swarm intelligence. Secondly, we introduce the research contents of cooperative control of multi-unmanned vehicle system. Then the research status of cooperative control of multi-unmanned vehicle system in the domestic and overseas are introduced. Finally, this dissertation summarizes the mainstream types of architecture and algorithm of the multi-unmanned vehicle system.